Physicochemical characterization of Majorcan Black Pig lard - Jaume J.; Garí F.; González J.; Sola L. (7th International Symposium on the Mediterranean Pig, 2012)
The Ensaimada de Mallorca is a typical sweet from the Island, made of flour and animal fat, and it is covered by a Protected Geographical Indication. Its name derives from saïm, which means pork lard in Catalan, and until the first half of the twentieth century it came exclusively from Majorcan Black Pigs. Currently, the Majorcan Black Pig lard is not used any more in the elaboration of Ensaimada. In the present study the physicochemical properties and thermal behaviour of fat from Majorcan Black Pigs were determined. The effect of the different origins of fat tissue from the pig carcass (flare fat vs intermuscular fat) on the elaboration process and quality of Ensaimada was assessed, using a reference scale set up by the Regulatory council of the Ensaimada de Mallorca. The results obtained showed that the physicochemical characteristics and behaviour of fat from Majorcan Black Pig were dependent on the type of fat tissue used in its preparation. The Majorcan Black Pig lard showed a monounsaturated fatty acid composition of 45.6% ± 2.6 in flare fat, and 50.9% ± 3.8 in intermuscular fat, due mainly to high oleic acid content. The type of fat that showed more similar characteristics and behaviours to those defined as the standard was the flare fat.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)